Influence of Harvesting on Quality of Alfalfa Forage used for Haylage and Hay - Aleksandar Vuković; Saša Barać; Petrović V. Dragan; Rade Stanisavljević; Dragoslav đokić; Rade Radojević (Journal of Agricultural Sciences)
The paper presents the three years efficiency results (2011-2013) of the work and ways of harvesting (three types of mowers, with or without spreading the forage) influencing the quality of the forage (the content of crude protein and crude fiber) during the three days drying process. These results indicate that the harvesting method can strongly affect the work efficiency, energy consumption, the forage drying intensity and the quality of forage used for hay and haylage preparation. The best quality of the forage was achieved when a drum rotating mower PÖTTINGER CAT 185 was used. Negative correlation was found between content of crude protein and the crude fibre content, depending on the type of mower, varying in the range between r= -0.978 and r= -0.882 (PÖTTINGER CAT 185 r= -0.882 P≤0.05 to JF STOLLSB 200 r= -0.978 P≤0.001).